Internet addiction among university students in Sungai Petani, Kedah / Mohd Asyraf Abd Khalid and Mohammad Amin Nasrin Md Yazid - Abd Khalid, Mohd Asyraf; Md Yazid, Mohammad Amin Nasrin (2019)
Internet addiction is becoming a global problem and has been associated with mental health issues such as depression and anxiety. There is a strong need for local research, given the recent rise of mental health issues amongst children and adolescents in Malaysia, as well as lack of research in this field locally. This study assessed the prevalence of internet addiction, and its association with internet-related factors, pornography, social media, and online gaming, amongst university in Sungai Petani, Malaysia. In this study, 300 university students were conveniently chosen from three selected university within Sungai Petani. A cross sectional survey was conducted on three selected universities. The numbers of questionnaire distributed is 300 completed questionnaires and each university divided into 100 on each university. The respondent completed the demographic profile as well as other section in the questionnaire consist of Internet Addiction, Pornography Factor, Social Media Factor and Online Gaming Factor. Pearson Correlation and Multiple Regression are carried out. This study found that Social Media (0.348), Online Gaming (0.243), and Pornography (0.226). Contrary to the previous studies, pornography factor has the lowest significant relationship on internet addiction among university student. As a conclusion, this study has important implications in relations to clinical practices, research and policy making in Malaysia